Analyzing arguments on tobacco tax increases. Focus on French parliamentary questions and responses, 2000–2020 - François Topart; Emmanuelle Béguinot; Karine Gallopel-Morvan (Tobacco Induced Diseases)
Introduction Tax increases are the most effective but still the least-used tobacco control measure. The tobacco industry (TI) employs lobbying strategies to oppose the implementation of tax policies on its products. Over the past two decades, French tobacco tax policies have been characterized by a relative inconsistency. This research aims to understand why, by analyzing the arguments of French policymakers (MPs and government) between 2000 and 2020 in favor or against tax increases.